2013
DOI: 10.1016/j.cor.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Branch and bound for the cutwidth minimization problem

Abstract: -The cutwidth minimization problem consists of finding a linear layout of a graph so that the maximum linear cut of edges (i.e., the number of edges that cut a line between consecutive vertices) is minimized. This paper starts by reviewing previous exact approaches for special classes of graphs as well as a linear integer formulation for the general problem. We propose a branch and bound algorithm based on different lower bounds on the cutwidth of partial solutions. Empirical results with a collection of previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Aside from using a MIP-based approach directly to solve the problem, a combinatorial branch-and-bound algorithm could be an interesting idea. Such approaches, which typically work with partial labelings and use problem-specific, graph-theoretic bounds for the problem at hand often are often quite effective for graph labeling problems (Caprara and Salazar-González 2005;Martí et al 2010Martí et al , 2013. In case of the ABP, even solving NP-hard problems within the branch-and-bound to provide bounds could be a viable option, since our computational study showed, that the stable set problem and graph coloring problem can be solved very quickly for the standard benchmark instances of the ABP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from using a MIP-based approach directly to solve the problem, a combinatorial branch-and-bound algorithm could be an interesting idea. Such approaches, which typically work with partial labelings and use problem-specific, graph-theoretic bounds for the problem at hand often are often quite effective for graph labeling problems (Caprara and Salazar-González 2005;Martí et al 2010Martí et al , 2013. In case of the ABP, even solving NP-hard problems within the branch-and-bound to provide bounds could be a viable option, since our computational study showed, that the stable set problem and graph coloring problem can be solved very quickly for the standard benchmark instances of the ABP.…”
Section: Discussionmentioning
confidence: 99%
“…In such problems, we are given a graph and we want to find a labeling (i.e., a numbering of its vertices), such that a given objective function is optimized. Problems in this class include the bandwidth problem (Cuthill and McKee 1969;Caprara and Salazar-González 2005) and variants of it like cyclic bandwidth (Rodriguez-Tello et al 2015), the linear arrangement problem (Caprara et al 2011;Rodriguez-Tello et al 2008) and the cutwidth problem (Martí et al 2013), see also the surveys (Díaz et al 2002;Gallian 2009). In this work, we consider the antibandwidth problem (ABP), also known as dual bandwidth problem (Yixun and JinJiang 2003), separation problem (Miller and Pritikin 1989) and maximum differential coloring problem (Bekos et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These optimization criteria ensure that the successor relations are mostly kept intact and at the same time successors are placed close to each other in the solution. Both problems the Minimum Feedback Arc Set Problem [ 37 ] and the Average Cut-Width Minimization Problem [ 59 – 61 ] are known to be NP-hard. Cutwidth minimization problems ask for a linear ordering of the vertices of a graph such that the average or maximum number of edges spanning across the gap between a pair of consecutive vertices is minimized.…”
Section: Theorymentioning
confidence: 99%
“…The problem of minimizing the average cut width [6] is also known to be NP-hard. A good heuristic [7] is necessary for good results. In our case, starting our procedure with the "primary path" taken by the reference genome is a natural choice.…”
Section: Problem Statementmentioning
confidence: 99%
“…The appendix provides a dependence of the number of feedback arcs and cut widths of number of variations of the same type. For this study, the number of variations of all types, except the examined, were fixed at level 7, and the number of investigated variations were changing according to the following list: 7,9,11,13,15,17…”
Section: Test Data Set Modellingmentioning
confidence: 99%